Contextual Hermeneutics of Beauty Privilege in Hadith through Gadamer’s Lens - Aulia Malikal Bilqis; Isvina Vawaidatur Rohmah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This article aims to interpret the hadith, “Allah swt. does not look at your appearance or your wealth, but rather at your heart and your deeds,” through Hans-Georg Gadamer’s philosophical hermeneutic approach. This approach emphasizes the importance of dialogue between the historical context of the hadith (the horizon of the text) and the social reality of modern readers (the horizon of the reader) as a dynamic process of understanding. This study employs a qualitative library-based method with a descriptive-hermeneutic analysis technique. The hadith is examined within its historical and social context, then brought into dialogue with the contemporary phenomenon of beauty privilege in the digital era. The results show that the message of the hadith remains relevant in critiquing the visual and materialistic culture that values individuals based on physical appearance and economic status. The deeper meaning of the hadith affirms that human worth is determined by sincerity of heart and righteous deeds, not by appearance or wealth. Gadamer’s hermeneutical approach enables this hadith to remain alive, relevant, and transformative within modern socio-religious discourse.